To smack or not to smack, is that the question? : the social perspectives on the issue of child discipline held by a cohort of mothers in Aotearoa New Zealand and what they indicate : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Thompson, Patricia (Massey University, 2015)
The response to the legislative change in New Zealand that occurred in 2007 on the physical discipline of children precipitated more public submissions to the government than any other piece of legislation in New Zealand history. The debates over the Crimes (Substituted section 59) Amendment Act 2007 (formerly known as section 59 of the Crimes Act 1961) provided a social context for this study of what contributed to the intense national debates within academia, families, and public arenas over such issues as children’s rights, parental rights, the socialisation of children, religion and the role of government. Parenting styles and the effectiveness and outcomes of smacking were a particular focus of much of this debate. This research was undertaken in the context of these debates, and established five research aims for a thesis that set out to explore the connections between mothers’ viewpoints on physical discipline and the wider issues that surround the complex and often contradictory spaces where the physical discipline of children is debated and discussed. The first four aims were addressed through four detailed reviews of literature with the overall purpose of breaking down and laying out the complexity of the debates that underpin any understanding of child discipline. The first review highlighted definitional issues relevant to this thesis, and included statutory definitions where appropriate. The second review explored and outlined evidence from a wide range of literature that contextualised the issue of physical discipline in and through the legislative debates surrounding the Crimes (Substituted section 59) Amendment Act 2007 in New Zealand. The third review outlined conceptual frameworks through which issues of child socialisation and discipline are commonly explained in order to frame the previous legislative discussion from a different perspective. The fourth and final review piece examined the issue of physical discipline and its potential impact on children and their socialisation. The abductive nature of this research meant that there was recursive movement between the empirical research and the bodies of literature that surround the research question. For the purposes of presentation, the literature reviews are introduced at the outset whereas they were undertaken before, after and during the empirical Q work. The summation of insights from the literature reviews, however, set the scene for the final aim, to identify the social perspectives on the issue of child discipline held by a cohort of mothers in New Zealand. They provide context for further understanding the identified social perspectives on the issue of child discipline held by a cohort of mothers in New Zealand through the social perspectives that emerged. The substantive field work undertaken to ground the conceptual material outlined through the reviews explored the attitudes and beliefs of mothers towards physical discipline and sought to identify explanatory inferences that could be drawn from those social perspectives in relation to the sharp divide amongst mothers in New Zealand about the use of physical discipline when raising children. This thesis, both the reviews and the field work components, relied on abductive logic generally and the use of Q-methodology specifically to elicit the social perspectives from the cohort of mothers. These revealed perspectives were then read against a range of social theories including Bronfenbrenner’s bio-ecological theory and attachment theory, amongst others. Two clear social perspectives were identified through the Q analysis: “a smack is more than a smack” and “a smack is nothing more than a smack”. These viewpoints were explored in relation to the wider literature on physical discipline, which pointed to the grey area between physical discipline and child abuse. Many of the issues dealt with in the literature assume the importance of specific behaviours including such things as whether a child was smacked with the palm of the hand or an implement, either on the buttocks or near the face, the severity of the smack, the age of the child, the anger of the parent, how harsh or how many smacks and, sporadically, the context in which the smack took place. Traditionally, little attention has been given to the wider socialisation processes reflected through the attitudes and beliefs of the mother and her relationship with the child. It is argued in this thesis that: (1) conversations about the physical discipline of children need to shift from assumptions about what constitutes physical discipline to the establishment of a clear definition of physical discipline in order for useful research to be undertaken, and only once this is done, to (2) consider how a light smack may (or may not) impact on relationships with children, what it teaches (both parents and children) through socialisation processes about how to relate, and what such discipline indicates for intrapersonal and interpersonal relationships during times of frustration or conflict that arise when parenting. By providing a more nuanced study of this controversial issue, the findings from this research contribute to a more socially embedded understanding of parent child relationship and the thesis adds a new perspective to the existing literature on the physical discipline of children. Encouraging consideration of socialisation processes rather than the nature of ill-defined disciplinary behaviours have significant implications for social policy and family support development both nationally and internationally.
Keywords: Discipline of children; corporal punishment; New Zealand